2021
DOI: 10.46347/jmsh.2021.v07i02.008
|View full text |Cite
|
Sign up to set email alerts
|

Health Status of Children Residing at Orphanages in Rural Karnataka

Abstract: Introduction: It is estimated that there are around 140 million children are orphans worldwide. These children suffer from physical neglect, poor hygiene, and a lack of nutrition, which result in various health problems among children. They are more prone to malnutrition, respiratory tract infection, skin diseases, and dental caries. Aim: This study aims to assess the health status among children living in an orphanage. Methods: A cross-sectional study was conducted at Kanyana residential ashrams or orphanages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…It is found that the joint family system still prevails in the weavers' community. The weaving occupation is one such profession which involves all the family members, be it children or the elderly, all of whom contribute their valuable services in the pre-loom, loom and post-loom processes (Singh & Naik, 2010). Considered to be CBE, these entrepreneurs not only make an important contribution to the local economy but also strengthen social ties within the community (Hertel et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that the joint family system still prevails in the weavers' community. The weaving occupation is one such profession which involves all the family members, be it children or the elderly, all of whom contribute their valuable services in the pre-loom, loom and post-loom processes (Singh & Naik, 2010). Considered to be CBE, these entrepreneurs not only make an important contribution to the local economy but also strengthen social ties within the community (Hertel et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The weaving occupation is one such profession which involves all family members from children to the elderly, all of whom contribute their valuable services in pre-loom, loom and post-loom processes (Singh & Naik, 2010) (Annexure, Figure A1). The weavers of Jharkhand form a part of a community of micro-entrepreneurs whose skill in their craft has seen their business grow over the years not just nationally but also internationally.…”
Section: Introductionmentioning
confidence: 99%